Peanut Variety Performance in Florida, 2004 - 2007 - Barry Tillman; Dan Gorbet; Mark Gomillion; Justin McKinney; George Person; Bill Thomas (EDIS, 2009)
SS-AGR-311, an 8-page illustrated report by Barry Tillman, Dan Gorbet, Mark Gomillion, Justin McKinney, George Person, and Bill Thomas, provides data from University of Florida peanut variety trials conducted in Florida at IFAS research centers located in Gainesville (Citra), Marianna, and Jay from 2004-2007. Published by the UF Department of Agronomy, December 2008. Reviewed April 2011.